Effect of nimodipine on ocular blood flow and colour contrast sensitivity in patients with normal tension glaucoma. Issue 1 (21st December 2004) - Luksch, A; Rainer, G; Koyuncu, D; Ehrlich, P; Maca, T; Gschwandtner, M E; Vass, C; Schmetterer, L
Abstract : Aim: To investigate the effects of oral nimodipine on ocular haemodynamic parameters and colour contrast sensitivity in patients with normal tension glaucoma (NTG). Design: The study was performed in a randomised, placebo controlled, double masked, crossover design. Participants: Nimodipine (60 mg) or placebo was administered to 14 consecutive NTG patients. Methods: The effects or oral nimodipine or placebo on ocular and systemic haemodynamic parameters and colour contrast sensitivity along the tritan axis were studied two hours after administration. Optic nerve head blood flow (ONHBF) and choroidal blood flow (CHBF) were assessed with laser Doppler flowmetry. Ocular fundus pulsation amplitude (FPA) was measured with laser interferometry. Colour contrast sensitivity (CCS) was determined along the tritan colour axis. Main outcome measures: ONHBF, CHBF, FPA, intraocular pressure and CCS were assessed in patients with NTG. Results: Mean ocular FPA increased by 14% (SD 14%) (p = 0.0008), ONHBF by 18% (SD 16%) (p = 0.0031), and CHBF by 12% (SD 14%) (p<0.001) after administration of nimodipine. Nimodipine also decreased the threshold of colour contrast sensitivity along the tritan colour axis (−14% (SD 12%); p = 0.048). However, individual changes in FPA, ONHBF, or CHBF were not correlated with changes in threshold of CCS along the tritan colour axis. Conclusions: The results indicate that nimodipine increases ONH and choroidal blood flow in NTG patients and improves CCS. The latter effect does not, however, seem to be a direct consequence of the blood flow improvement.